Preparasi dan Karakterisasi Bioplastik dari Limbah Ekstraksi Karagenan Rumput Laut Kappaphycus alvarezii (Doty) Doty ex P. C. Silva, 1966 dengan Pemlastis Gliserol - Ali Ridlo; Agus Sabdono; Subagiyo Subagiyo; Raden Ario; Ibnu Pratikto; Retno Hartati (Jurnal Kelautan Tropis, 2024)
The carrageenan production process from Kappaphycus alvarezii seaweed produces solid waste of 60%-70% w/w, primarily composed of cellulose, which can be used for bioplastic films. This research aims to determine the effect of glycerol plasticizer addition on the characteristics of K. alvarezii waste-based bioplastics. Bioplastics were made by mixing 50 g of wet waste with 90 mL of distilled water, homogenized at 70°C for 30 minutes. Glycerol (0%, 1%, 2%, 3%, 4%) was added, with water to a total volume of 150 mL, and homogenized again for 30 minutes. The solution was poured into a polypropylene mold and dried at 60°C for 24 hours. Results showed glycerol increased transparency and elongation but reduced tensile strength and water resistance. The addition of 1% glycerol produced bioplastics with the best characteristics, meeting Japanese Industrial Standards. FTIR and SEM showed similar bioplastic properties across treatments. This research indicates that K. alvarezii carrageenan extraction waste is promising for packaging material and bioplastic production.